2014
DOI: 10.1021/tx500287f
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Nanoparticle Inhalation Induces Renal Fibrosis in Mice via an Oxidative Stress Upregulated Transforming Growth Factor-β Pathway

Abstract: Titanium dioxide nanoparticles (Nano-TiO2) are gradually being used extensively in clinical settings, industry, and daily life. Accumulation studies showed that Nano-TiO2 exposure is able to cause injuries in various animal organs, including the lung, liver, spleen, and kidney. However, it remains unclear whether exposure of Nano-TiO2 by inhalation causes renal fibrosis. Here, we investigated the role of reactive oxygen species (ROS)/reactive nitrogen species (RNS) related signaling molecules in chronic renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 80 publications
1
39
1
Order By: Relevance
“…Consistently with in vitro studies, experiments in mice also showed that titanium induces increased expression of pro-inflammatory cytokines (TNFα, IL-1β and IL-6), chemokines (CCL2 and CCL3), NLPR3, ROS and RNS (Huang et al, 2015, Jovanovic, 2015, Sang et al, 2012, Warme et al, 2004, Yazdi et al, 2010.…”
Section: 1immune Response To Titaniumsupporting
confidence: 77%
“…Consistently with in vitro studies, experiments in mice also showed that titanium induces increased expression of pro-inflammatory cytokines (TNFα, IL-1β and IL-6), chemokines (CCL2 and CCL3), NLPR3, ROS and RNS (Huang et al, 2015, Jovanovic, 2015, Sang et al, 2012, Warme et al, 2004, Yazdi et al, 2010.…”
Section: 1immune Response To Titaniumsupporting
confidence: 77%
“…Our previous studies suggested that exposure to anatase TiO 2 NPs (5–6 nm) for 2 weeks, 3, or 6 months caused significant elevations in serum Cr and proteinuria in mice, and renal inflammation in female mice, but we did not observe renal fibration . Recently, intratracheal exposure to TiO 2 NPs (21 nm with 35 − 65 m 2 /g surface area, 0.25, and 0.5 mg/week) for four weeks or gavage exposure to TiO 2 NPs (5–6 nm with 174.8 m 2 /g surface area, 1.25, 2.5, or 5 mg/kg body weight) for 9 months was found to result in renal inflammation and fibrosis of male, or female mice . However, bulk TiO 2 (5 μm) did not increase renal histopathological changes in mice .…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 was previously considered to be nontoxic in particle toxicology; however, it has been recently classified by the International Agency for Research on Cancer as “possibly carcinogenic to humans” by inhalation, and its multiple specific characteristics coupled with unknown risks to human health and the environment have been reported . While TiO 2 NPs inhalation exposure has been suggested to cause renal damage in mice …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today the mechanism of action of titanium on the human body is not yet fully understood, but it is known that metal can cause adverse health effects as a result of, for example, inhalation (Grassian et al, 2007;Huang et al, 2015;Ma-Hock et al, 2007;Wang et al, 2007;Warheit et al, 2007). Titanium alloys are of great value in orthopedic surgery due to their significant resistance to the attack of body fluids, strength, flexibility, biocompatibility, or lack of allergenicity (Niinomi, 2008).…”
Section: Introductionmentioning
confidence: 99%